Antihyprtensive Activity Of Para-substituted Clonidine Analogues And Their Acylated Derivatives - Lewis, Alan Martin (1994)
The use of clonidine in antihypertensive drug regimens has been severely limited by tr.e appearance of withdrawal hypertension upon, abrupt discontinuation of treatment.